Power Net Station / Fatima Jamleh ... [et al.] - Jamleh, Fatima; Justin Likob, Joanna; Jumana, Mohd. Sharul; Miasin, Norsimah (2014)
Our company's name is Power Net Station and we are providing Internet service to everyone, which are mostly students and bachelors. Our business location is at Lot 13A-B, 1st Floor, University Plaza, Jalan Sulaman, 88450 Kota Kinabalu, Sabah.We perform a partnership business for this Internet service. Each of us had our own tasks and responsibilities in every position, whereby General Manager is Mohd. Sharul Bin Jumana, Administrative Manager is also Mohd. Sharul Bin Jumana, Marketing Manager is Norsimah Binti Miasin, Operation Manager is Fatima Binti Jamleh, and Financial Manager is Joanna Justin Likob. Each of this position is very important to ensure the business objective, vision and mission can be achieved. In this partnership business, we already make an agreement which is agreed by every member. Apart from that, in our administrative department we also have an incentive scheme for employees to encourage them to be more responsible and have high commitment in carrying out their job. We had offer employees' incentive scheme like Employees Provident Fund (EPF), Social Security Organization (SOCSO), bonus, maternity and paternity leave, annual leave, and medical leave. Besides that, we make a proper plan for each department to ensure the business objective can be achieved. Marketing plan involved the market size of the bus~ness, competitors, target market, and strategies in promoting business The proper marketing plan will know and choose the best strategies to promote business with knowledge of how to excellently compete with other competitors. The strategies that we use to promote our business are through signboard, business cards, and also mass media like website. Furthermore, we also make a proper operation plan which includes operation process planning, material planning, locations planning and so on. Overall function of the operation plan is to ensure that the resources can be allocated in effective and efficient ways to prevent wastage of resources. In additional, choosing the best location for operating business is also very important, because it will involves a lot of cost to the entire business. Moreover, we also ensure that we make a proper financial planning. Through the financial planning we can determine the development ad achievement of the business that we had planned. Financial will involves of the cost needed for every department like administration budget, marketing budget, and also operational budget. All of the data are very important to prepare financial projection for the current time period and also in the future. It also provided a clear estimation for amount of money needed to start and run a business. In additional, each of us decided to contribute our own equity to the business in order to make the business run smoothly and hoping that it will reduce our expenses. Each of the partner have contributed total of RM 10,000.00 contribution in form of fixed assets and cash money. Therefore, each department must carry out their own tasks and responsibilities in order to accomplish the business goals. All partners have sacrificed time, energy, and personal money to ensure that this business plan will be done very well. We hope that this business plan could bring success to achieve our goals.